Study on the Prospects of Use the Group D Engine Oil in Locomotive Diesel Engines - Ðšravets, Andrii; YÐµvtushenko, Andrii; Pogrebnyak, Andrii; Romanovych, Yevhenii; Afanasov, Heorhii (International Journal of Engineering and Technology, 2018)
It was suggested to use group D engine oil with advanced properties instead of group V and G engine oils, which are used in locomotive diesel engines today, to improve the performance of the Ukrainian locomotive fleet of railways.A series of comparative laboratory studies of these oil groups was conducted to substantiate this suggestion which proved better lubrication and tribological performance of group D engine oil and allowed its performance tests.Tests conducted on diesel 5D49 for mileage of more then 100,000 km have demonstrated the advantages of group D oils, such as more stable viscosity, neutralizing ,washing and other properties. Studies on the four-ball wear test machine proved better anti-wear, anti-scoring and anti-friction properties of group D engine oil, which appear even after the continuous use of oils in locomotive diesels. Decrease in burning loss of engine oil was recorded, resulting in the decrease of oil fuel consumption for group D by 30-60% vs. the group G oil.According to the results of performance tests, group D engine oil has been recommended for the use in 5D49 locomotive diesels and some advice on its future implementation have been provided.Â Â